Continuous Quadrupole Magnetic Separation of Islets during Digestion Improves Purified Porcine Islet Viability - Bradley P. Weegman; Venkata Sunil Kumar Sajja; Thomas M. Suszynski; Michael D. Rizzari; William E. Scott III; Jennifer P. Kitzmann; Kate R. Mueller; Thomas R. Hanley; David J. Kennedy; Paul W. Todd; Appakalai N. Balamurugan; Bernhard J. Hering; et al. (Journal of Diabetes Research)
Islet transplantation (ITx) is an emerging and promising therapy for patients with uncontrolled type 1 diabetes. The islet isolation and purification processes require exposure to extended cold ischemia, warm-enzymatic digestion, mechanical agitation, and use of damaging chemicals for density gradient separation (DG), all of which reduce viable islet yield. In this paper, we describe initial proof-of-concept studies exploring quadrupole magnetic separation (QMS) of islets as an alternative to DG to reduce exposure to these harsh conditions. Three porcine pancreata were split into two parts, the splenic lobe (SPL) and the combined connecting/duodenal lobes (CDL), for paired digestions and purifications. Islets in the SPL were preferentially labeled using magnetic microparticles (MMPs) that lodge within the islet microvasculature when infused into the pancreas and were continuously separated from the exocrine tissue by QMS during the collection phase of the digestion process. Unlabeled islets from the CDL were purified by conventional DG. Islets purified by QMS exhibited significantly improved viability (measured by oxygen consumption rate per DNA, p<0.03) and better morphology relative to control islets. Islet purification by QMS can reduce the detrimental effects of prolonged exposure to toxic enzymes and density gradient solutions and substantially improve islet viability after isolation.